PHASE II, RANDOMIZED, PLACEBO-CONTROLLED, 90-DAY STUDY OF EMIXUSTAT HYDROCHLORIDE IN GEOGRAPHIC ATROPHY ASSOCIATED WITH DRY AGE-RELATED MACULAR DEGENERATION. Issue 6 (June 2015) - Dugel, Pravin U.; Novack, Roger L.; Csaky, Karl G.; Richmond, Preston P.; Birch, David G.; Kubota, Ryo
Abstract : Purpose: This study assessed the safety, tolerability, and pharmacodynamics of emixustat hydrochloride (ACU-4429), a novel visual cycle modulator, in subjects with geographic atrophy associated with dry age-related macular degeneration. Methods: Subjects were randomly assigned to oral emixustat (2, 5, 7, or 10 mg once daily) or placebo (3:1 ratio) for 90 days. Recovery of rod photoreceptor sensitivity after a photobleach was measured by electroretinography. Safety evaluations included analysis of adverse events and ophthalmic examinations. Results: Seventy-two subjects (54 emixustat and 18 placebo) were evaluated. Emixustat suppressed rod photoreceptor sensitivity in a dose-dependent manner. Suppression plateaued by Day 14 and was reversible within 7 days to 14 days after drug cessation. Most systemic adverse events were not considered treatment related. Dose-related ocular adverse events (chromatopsia, 57% emixustat vs. 17% placebo and delayed dark adaptation, 48% emixustat vs. 6% placebo) were mild to moderate in severity, and the majority resolved on study or within 7 days to 14 days after study drug cessation. Reversibility of these adverse events with long-term administration, however, is undetermined. Conclusion: In this Phase II study, emixustat produced a dose-dependent reversible effect on rod function that is consistent with the proposed mechanism of action. These results support further testing of emixustat for the treatment of geographic atrophy associated with dry age-related macular degeneration. Abstract : Supplemental Digital Content is Available in the Text.Emixustat hydrochloride (ACU-4429) slowed visual cycle activity in a dose-dependent manner in subjects with geographic atrophy associated with dry age-related macular degeneration. Commonly occurring adverse events were ocular; all were mild to moderate in severity and typically resolved despite continued dosing or within 7 days to 14 days after study drug cessation.